Optimizing Health and Safety Inspections in Canada - Bouchard St-Amant, Pier-André (International Journal of Occupational Safety and Health, 2017)
Background: Each year, the Canadian government assigns inspectors to visit firms and ensure compliance to the occupational health and safety provisions of the Canada Labour Code. This paper presents evidence supporting the hypothesis that assignments reduce the number of disabling injuries. It also presents a mathematical technique improving the performance of how firms are chosen for inspection. Methods: By combining two administrative databases covering worksites under federal jurisdiction, the impact of assignments on injuries is estimated using instrumental variables. The instruments are the exogenous part of the government’s assignment rule for inspectors. Results: The impact of one assignment on injuries is estimated to be -0.33 in the year following the assignment. Furthermore, by introducing a measure of diminishing marginal returns of assignments by sector, a more efficient assignment rule to help further minimize the number of injuries resulting from non-compliance with the Labour Code is suggested. This improved rule includes a reallocation of assignments across industries compared to the current allocation. In particular, assignments are transferred from the sectors of Air Transport and Road Transport to the sectors of Banking, Postal Contractors and Crown Corporations. Conclusions: A counterfactual experiment with the new allocation of assignments suggests an 18% decrease in the number of injuries for the same yearly average number of assignments. Based on available estimates of the cost of injuries, the suggested change in the targeting tool would lead to annual savings of 72 million dollars in workers’ compensation claims.